An early marker of fetal infection after primary cytomegalovirus infection in pregnancy. Issue 6522 (15th March 1986) - Stern, H; Hannington, G; Booth, J; Moncrieff, D
Abstract : Fourteen patients with primary cytomegalovirus infection diagnosed by serological screening at antenatal attendances were examined for their responses in the lymphocyte transformation test against cytomegalovirus. Tests were done during pregnancy, shortly after the diagnosis of primary infection. Eight women showed positive lymphocyte transformation responses and gave birth to uninfected babies. Six showed negative responses and four of the babies were born congenitally infected. Cellular immunity therefore plays a part in preventing intrauterine transmission of cytomegalovirus, and its depression after primary infection in the mother during pregnancy may be used as an early marker of fetal infection.